Recruiting and retaining labour in agricultural businesses : a multiple case study of employer branding in swedish agriculture - Engvall, Marcus; Krumlinde, Olof (SLU/Dept. of Economics, 2020)
There is an increasing need for competent workforce in the agricultural sector, but a lack of potential candidates on the labour market. In June 2017, the Swedish state adopted a new national food strategy. This strategy points out the direction of the Swedish food policy until 2030. The overall goal of the strategy is to create a competitive food sector that increases food production in Sweden and contributes to sustainable development. With this goal, the strategy also aims to create more jobs and sustainable growth in the Swedish food supply chain. However, the Federation of Swedish Farmers presented a report in 2018 saying that there is a lack of labour in the Swedish agricultural industry. In fact, 8 out of 10 companies in the sector found it hard to attract and acquire competent labour, according to the report. The problem of not finding the right employees can inhibit the development opportunities for the companies. The companies in the agricultural sector needs to be associated with a positive employment experience and differentiate their identity as employers to become more attractive to potential employees. To create a competitive edge in recruiting and retaining employees, companies can invest time and resources in employer branding practices to become and remain a desired employer in the eyes of the employee. The aim of this study is to investigate employer branding practices to attract, recruit and retain employees in Swedish agricultural businesses. The goal of this aim is to understand how agricultural businesses work to attract and retain employees with the right competence by using employer branding practices. With a qualitative research approach this study investigates the employer branding practices of eight different cases consisting of farmers in the region of Mälardalen, Sweden. A theoretical framework consisting of theories within employer branding has been created in order to identify different components and give an understanding of how farmers work with employer branding practices in the processes of recruiting and retaining employees. Key findings are that farmers in Sweden invest in their employer brand and develop employer branding strategies and activities. The companies develop their employee value propositions, consisting of attributes and promises that makes them attractive to the targeted audience of potential employees. The proposition includes both tangible and intangible benefits such as accommodation, flexible working hours and good workplace culture. The companies also do their best to fulfil these promises throughout the employment to motivate and develop the staff, with a goal to increase retention and create value for the organization. The most important part of the employer brand, according to the respondents, were their reputation as an employer. Thus, to increase the employer attractiveness, there is a great opportunity for improvement by engaging further in employer branding practices that benefits the reputation as an employer.